Dexamethasone and Phorbol Ester, but not Cytokines, Increase the Production of Plasminogen Activator Inhibitor Type-2 in the PL-21 Human Promyelocytic Leukemia Cell Line - Niiya, Kenji; Takeuchi, Tetsuo; Kobayashi, Makoto; Miyoshi, Isao; Hayashi, Tomohiro; Sakuragawa, Nobuo (Thrombosis and Haemostasis, 1991)
PL-21 is a promyelocytic leukemia cell line that produces plasminogen activator inhibitor 2 (PAI-2). Differentiation-linked expression of PAI-2 was investigated by adding cell-differentiation promoting agents [such as phorbol myristate acetate (PMA), retinoic acid (RA), dexamethasone (Dex), and recombinant cytokines, including tumor necrosis factor-α (TNF-a), transforming growth factor-β (TGF-β), granulocyte-colony stimulating factor (G-CSF), and interleukin-6 (IL-6)] into the culture medium of PL-21 cells. PAI-1 and PAI-2 antigens were measured by an enzyme-linked immunoassay. The PAI-1 antigen, however, became detectable only after stimulation. The presence of PAI-2 antigen was further verified by immunoblotting using a monoclonal antibody against PAI-2 purified from a PL-21 culture medium. PAI activity both in the culture medium and in the cell lysate increased approximately 70-fold after exposure to PMA. Both PAI-1 and PAI-2 antigens increased, but the amount of the latter in the culture medium and in the cell lysate was approximately 10 times and 2,500 times, as much, respectively, as that of the former. Dex also increased the intracellular PAI activity approximately 6-fold, parallel with PAI-2 antigen. PAI-1 antigen increased only slightly in the culture medium but not in the cell lysate after Dex-stimulation. As with the case of PMA, TNF-a and IL-6 induced PL-21 cells to macrophage-like cells, but did not affect the PAI activity. Thus, the increase of the PAI-2 production by PMA may not necessarily depend on differentiation into macrophages. Other cytokines examined did not increase the PAI activity. Glucocorticoid has various effects on the fibrinolytic system because it has been also shown that the mRNA of PAI-2 in a human fibrosarcoma cell line decreases in response to Dex.